Molecular genetic study of the frequency of monosomy 22q11 in DiGeorge syndrome. - Carey, A; Kelly, D; Halford, S; Wadey, R; Wilson, D; Goodship, J; Burn, J; Paul, T; Sharkey, A; Dumanski, J (1992)
It is well established that DiGeorge syndrome (DGS) may be associated with monosomy of 22q11-pter. More recently, DNA probes have been used to detect hemizygosity for this region in patients with no visible karyotypic abnormality. However, DGS has also been described in cases where the cytogenetic abnormality does not involve 22q11; for instance, four cases of 10p- have been reported. In this study we have prospectively analyzed patients, by using DNA markers from 22q11, to assess the frequency of 22q11 rearrangements in DGS. Twenty-one of 22 cases had demonstrable hemizygosity for 22q11. Cytogenetic analysis had identified interstitial deletion in 6 of 16 cases tested; in 6 other cases no karyotype was available. When these results are combined with those from our previous studies, 33 of 35 DGS patients had chromosome 22q11 deletions detectable by DNA probes.